THE ROLE OF A TRANSFORMATIVE APPROACH IN THE DEVELOPMENT OF GRAPHIC COMPETENCE IN FUTURE TECHNOLOGICAL EDUCATION TEACHERS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes changes throughout the higher education system. Concerning continued education, transformational approaches are discussed aimed at introducing digital didactics and distance education, solving problems that arose during the pandemic, as well as increasing personal development and social activity. The author's article is cited as an important factor in bringing the changes that are taking place in society to a new level by correlating the transformation of socio-cultural technologies and the educational system. The transformation processes taking place on the example of Uzbekistan and new methods applied to higher education, serve to develop the country's development and the scientific and intellectual potential of its people.